VOLUNTARY DISCLOSURE IN INDONESIA: COMPARISON OF SHARIAH AND NON-SHARIAH COMPLIANT COMPANIES - Peni Nugraheni (Jurnal Akuntansi dan Auditing Indonesia, 2011)
Shariah compliant companies are companies which the activities are accordance with Shariah principles. Indonesia, through Bapepam issues Shariah Securities List containing companies which has fulfilled the Shariah requirements issued by regulators. This study attempts to find out the practice of voluntary disclosure of the Shariah compliant companies and identifies the differences with the practice of non-Shariah compliant companies. This research investigates the quantity and quality of voluntary disclosure in the annual reports of Shariah compliant companies listed in Indonesian Stock Exchange and compare it with non-Shariah compliant companies. Voluntary disclosures were measured using 30 items of disclosure index developed by Khomsiah (2005). Based on content analysis of 2009 annual report of 55 Indonesian listed companies for each category, the finding describes the differencse in the quantity and quality of voluntary disclosure value of Shariah and non-Shariah compliant companies. Shariah compliant companies disclose more items and have higher quality of disclosure than non-Shariah compliant companies.Keywords: Shariah compliant companies, voluntary disclosure, content analysis  Perusahaan yang kegiatan operasinya sesuai dengan prinsip Syariah (Shariah compliant companies) adalah emiten atau perusahaan publik yang kegiatannya sesuai dengan prinsip Syariah. Bapepam telah menerbitkan Daftar Efek Syariah yang memuat kumpulan efek yang tidak bertentangan dengan prinsip-prinsip Syariah di pasar modal. Studi ini bertujuan untuk mengetahui praktek pengungkapan sukarela oleh perusahaan yang sesuai Syariah dan membandingkannya dengan perusahaan non-Syariah yang terdaftar di pasar modal Indonesia. Kuantitas dan kualitas pengungkapan sukarela dalam 55 laporan tahunan tahun 2009 untuk masing-masing kategori diukur menggunakan content analysis melalui 30 indeks pengungkapan yang dikembangkan oleh Khomsiah (2005). Hasil penelitian menunjukkan bahwa perusahaan yang kegiatan operasinya sesuai dengan prinsip Syariah mengungkapkan lebih banyak item dengan kualitas yang lebih tinggi dibandingkan dengan perusahaan non-Syariah.Kata kunci: perusahaan Syariah, pengungkapan sukarela, content analysis